Añora, Spanien: Der Fundplatz ‚La Losilla‘ bei Añora (Córdoba) – eine spätantike Kirche im ländlichen Bereich der Baetica - Schlimbach, Fedor (e-Forschungsberichte des DAI, 2023)
The project deals with the remains of a church built in late antiquity, located at ‚La Losilla‘ near the village of Añora (Córdoba) in Andalusia. Beside the remainder of the church itself, particularly the necropolis is noteworthy. One significant aim of the project is to examine by archaeological means the context in which the church was built and used. The venture was started in early 2013 and will be pursued at least until autumn 2016. This article gives a résumé of the results gained during the campaign of 2013.